Pengaruh Gaya Indis Pada Interior Gereja Kristen Jawi Wetan Jemaat Surabaya - Enggar Hadi Prayogo (Intra, 2015)
Indies style is a style that has the special characteristic of the influence of colonial style that invaded the town of Java. GKJW Church Surabaya established in 1924, is located in Jl.Prof.Dr.Moestopo church where the location affected by the spread of culture Indies. The distinctive feature of the interior of the church that stands out from other GKJW Church, located on the square layout elongated linear shape, and experienced the formation to form a cross, with the concept of a centralized circulation to the linear circulation. This study aims to determine the extent of the effect of force on the interior GKJW Indies Church Surabaya, and what impact that occurs due to the influence Indies style. The method used by researchers, using qualitative methods produce descriptive form of words written or spoken of those that can be observed. The results showed that the style used church interior is a modern classic style, besides there are other styles which are Art and Craft, Art Deco, and Art Neoveau. The architecture of the building as a whole are affected Indies style.